2019
DOI: 10.1017/s0029665118002641
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene in the human body: metabolic bioactivation pathways – from digestion to tissue distribution and excretion

Abstract: 5Paprika Bioanalytics BT, Debrecen, Hungary β-Carotene intake and tissue/blood concentrations have been associated with reduced incidence of several chronic diseases. Further bioactive carotenoid-metabolites can modulate the expression of specific genes mainly via the nuclear hormone receptors: retinoic acid receptor-and retinoid X receptor-mediated signalling. To better understand the metabolic conversion of β-carotene, inter-individual differences regarding β-carotene bioavailability and bioactivity are key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 233 publications
(311 reference statements)
1
96
0
1
Order By: Relevance
“…The main biological functions of components such as α-and β-carotene are their pronounced pro-vitamin A activity [81,82], and a series of bioactive functions, especially antioxidant activity [83,84]. Along with its bioactive functions, C. moschata brings together fundamental characteristics for biofortification programmes, such as high production potentials and profitability, high efficiency in reducing deficiencies in micronutrients in humans, and good acceptance by producers and consumers in the regions where this crop is grown [8].…”
Section: Identification Of Promising Groups Of Genotypesmentioning
confidence: 99%
“…The main biological functions of components such as α-and β-carotene are their pronounced pro-vitamin A activity [81,82], and a series of bioactive functions, especially antioxidant activity [83,84]. Along with its bioactive functions, C. moschata brings together fundamental characteristics for biofortification programmes, such as high production potentials and profitability, high efficiency in reducing deficiencies in micronutrients in humans, and good acceptance by producers and consumers in the regions where this crop is grown [8].…”
Section: Identification Of Promising Groups Of Genotypesmentioning
confidence: 99%
“…Surprisingly, in this study calculating the individual correlation between the plasma values of ATRA with plasma levels of the main pro-vitamin A all- trans -β-carotene (ATBC, Figure S1 ) displayed no significant correlation determined in all individuals ( n = 40, healthy adults and AD-patients). Therefore, the connection between increased carotenoid intake with following increased plasma ATBC levels and further increased RAR- and RXR-mediated signalling seems to be questionable, like discussed and co-found in recent reports [ 4 , 23 ].…”
Section: Discussionmentioning
confidence: 96%
“…A direct functional comparison of found alterations of carotenoid plasma levels of data originating from adults, examined this study, and children [ 7 ] cannot be done because the levels found in children were determined to be much lower. If these reduced levels of carotenoids in AD-patients or atopic children are based on higher chronic inflammation and a further pro-oxidant stress, a targeted selected downregulation of carotenoid absorption and binding, a different occurrence of carotenoid-levels specific polymorphisms or reduced intake of healthy food [ 21 , 23 ], remains speculative. One possible mechanism might be that lutein/zeaxanthin are known to negatively interfere with ATRA-RAR-mediated signalling [ 65 , 66 , 67 ] which was associated with pro-allergic Th2 immune responses [ 1 , 6 , 9 , 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main biological functions of components such as α - and β -carotene are their pronounced pro-vitamin A activity [74, 75], and a series of bioactive functions, especially antioxidant activity [76, 77]. Along with its bioactive functions, C. moschata brings together fundamental characteristics for biofortification programmes, such as high production potentials and profitability, high efficiency in reducing deficiencies in micronutrients in humans, and good acceptance by producers and consumers in the growing regions [10].…”
Section: Discussionmentioning
confidence: 99%